A preparation method for a new composite material for signal hydrogen molecules
By performing high-temperature heat treatment and chemical modification of activated carbon fibers, a new signal hydrogen molecule fitting composite material was prepared, which solved the problem that hydrogen molecules are difficult to reach the lesion tissue in existing hydrogen medicine, and achieved the biocompatibility of the material and Antibacteriality, suitable for clinical applications of hydrogen medicine.
Patent Information
- Application Number
- CN202411163751.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-23
AI Technical Summary
In the existing hydrogen medicine, it is difficult to achieve the purpose of efficient arrival and accumulation of hydrogen molecules in large quantities in lesion tissues, and there are safety hazards and hydrogen concentration limitations.
By performing high-temperature heat treatment and chemical modification of activated carbon fibers, a new signal hydrogen molecule-fitting composite material with good biocompatibility and bacteriostatic properties was prepared. The material enhances hydrogen adsorption capacity through heat treatment and imparts biocompatibility and bacteriostatic properties through a series of chemical reactions.
It has achieved good adsorption of hydrogen, has significant antibacterial properties and good biocompatibility, and can supply hydrogen in the body, which is suitable for clinical applications in the field of hydrogen medicine.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular, relates to a method for preparing a new composite material carrying signal hydrogen molecules. Background Art
[0002] Signal hydrogen, or hydrogen, is a colorless, odorless and reducing gas at room temperature and pressure. Hydrogen has long been considered an inert gas. It was not until 1975 that Dole's research group successfully used high-pressure hydrogen to inhibit the proliferation of animal squamous cell carcinoma, proving for the first time that hydrogen can play a role in living organisms. However, due to the technical limitations at the time, the experiment did not clarify the mechanism of action of hydrogen in living organisms, and because the use of high-pressure hydrogen posed a safety hazard, no more research focused on the application of hydrogen in biomedicine. With the development of biomedicine, the biomedical effects of hydrogen have once again entered people's field of vision. In 2007, In 2005, Ohsawa's research group reported that extremely low concentrations of hydrogen can effectively protect rats from ischemia-reperfusion brain injury. Its mechanism of action is that hydrogen can selectively remove hydroxyl radicals and nitrite anions in the body. This discovery has promoted the rapid development of hydrogen in medicine. Since then, many laboratories around the world have successively proved that hydrogen is a new biological gas signal molecule that can treat important diseases and injuries such as cerebral ischemia, liver ischemia, small intestinal ischemia, inflammatory response after small intestinal transplantation, neonatal cerebral ischemia and hypoxia, arteriosclerosis, enteritis and human diabetes.
[0003] Currently, hydrogen medicine mainly uses hydrogen-rich water and hydrogen inhalation to provide hydrogen to patients. However, since hydrogen is easy to diffuse and almost insoluble in water, these two methods have not achieved good results and cannot achieve the purpose of hydrogen molecules effectively reaching and accumulating in large quantities in the lesion tissue. In addition, the method of drinking hydrogen-rich water also has the problem of limiting hydrogen concentration, which further increases people's concerns about the safety of hydrogen inhalation. Therefore, at this stage, there is an urgent need for a new material that can be used in clinical practice with good biocompatibility and can carry a large amount of hydrogen. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a new composite material that is compatible with signal hydrogen molecules. A new composite material that is compatible with signal hydrogen molecules is prepared, activated carbon fibers are heat treated to enhance their hydrogen adsorption capacity, and then the heat-treated activated carbon fibers are modified through a series of chemical reactions to obtain a new composite material with biocompatibility and antibacterial properties.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a new composite material for carrying signal hydrogen molecules, comprising the following steps:
[0007] Step 1: After washing the activated carbon fiber (ACF) with ultrapure water, lay it flat in a high-temperature tube furnace and perform heat treatment under nitrogen protection. After the heat treatment, cool it naturally to room temperature. After cooling to room temperature, boil the activated carbon fiber in ultrapure water to obtain modified activated carbon fiber (ACF);
[0008] Step 2: Add modified activated carbon fiber (ACF), dimethyl sulfoxide, and epichlorohydrin into a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, add sodium hydroxide solution into the three-necked flask, react at 50°C for 3 hours, and then vacuum filter. The solid obtained by filtration is washed with ethanol and dried to obtain intermediate 1.
[0009] The reaction process is as follows:
[0010]
[0011] Step 3: Add intermediate 1, 3-aminopropyltriethoxysilane and dioxane into a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at 50°C for 6 hours. After the reaction is completed, vacuum filter, wash the filtered solid with ethanol and dry it to obtain intermediate 2;
[0012] The reaction process is as follows:
[0013]
[0014] Step 4: Add intermediate 2, chlorododecane and sodium hydroxide solution into a three-necked flask, install a condenser and a thermometer, start magnetic stirring, react at 80°C for 72h, vacuum filter after the reaction, wash the filtered solid with ethanol and dry to obtain the composite new material;
[0015] The reaction process is as follows:
[0016]
[0017] Furthermore, the activated carbon fiber used in the first step has a diameter of 10-15 μm.
[0018] Furthermore, the temperature condition of the heat treatment in the first step is 800-1100°C.
[0019] Furthermore, the time condition of the heat treatment in the first step is 4-6 hours.
[0020] Furthermore, the boiling time in ultrapure water after the heat treatment in the first step is 45-60 minutes.
[0021] Furthermore, the sodium hydroxide solution in the second step is a sodium hydroxide aqueous solution with a molar concentration of 4 mol / L.
[0022] Furthermore, the amount ratio of the modified activated carbon fiber (ACF), dimethyl sulfoxide, epichlorohydrin, and sodium hydroxide solution used in the second step is: 3g:20-25g:2.1-2.4g:10-15g.
[0023] Furthermore, the usage ratio of the intermediate 1, 3-aminopropyltriethoxysilane, and dioxane used in the third step is: 3g:1.4-1.6g:30-35g.
[0024] Furthermore, the sodium hydroxide solution in the fourth step is a sodium hydroxide ethanol solution with a molar concentration of 2 mol / L.
[0025] Furthermore, the usage ratio of the intermediate 2, chlorododecane and sodium hydroxide solution used in the fourth step is 3g:1.6-1.8g:15-20g.
[0026] Furthermore, in the second step, the modified activated carbon fiber is replaced with a fiber structure with hydroxyl groups or a protein structure with hydroxyl groups, and hydrogen molecules are matched and loaded to obtain a new composite material.
[0027] Beneficial effects of the present invention:
[0028] 1) The present invention changes the surface properties and internal structure of the activated carbon fiber by subjecting the activated carbon fiber to high-temperature heat treatment. Under the high-temperature environment and the reducing effect of nitrogen, the polar functional groups on the surface of the activated carbon fiber will break and the number of internal pores will increase. According to the principle of "like dissolves like", the adsorption of non-polar hydrogen by the activated carbon fiber after high-temperature modification will be enhanced. Therefore, the modified activated carbon fiber can be used as a good hydrogen storage medium.
[0029] 2) The present invention allows the modified activated carbon fiber to react with epichlorohydrin under alkaline conditions to cause a nucleophilic substitution reaction between halogen and hydroxyl, so that the modified activated carbon fiber carries an epoxy group, and then the activated carbon fiber intermediate 1 with the epoxy group is subjected to a nucleophilic addition reaction with 3-aminopropyltriethoxysilane to obtain an organic silicon-modified activated carbon fiber intermediate 2, and finally the activated carbon fiber intermediate 2 with an organic silicon structure is subjected to a chemical reaction with chlorododecane under alkaline conditions to obtain a composite new material with a quaternary ammonium salt structure. The reaction is divided into two steps. The first step is that the imino group of the intermediate 2 is first subjected to a substitution reaction with chlorododecane, and the imino group is converted into a tertiary amine The tertiary amine structure obtained in the first step then reacts with an excess of halogenated dodecane to produce a quaternary ammonium salt reaction to obtain a new composite material; the composite material is modified with silicone, and its weather resistance is significantly enhanced. In addition, the material is also endowed with biocompatibility, so it can be used to supply hydrogen in the body. In addition, the composite material also has a quaternary ammonium salt structure with a double long-chain alkyl group, which is positively charged as a whole, so it has an adsorption effect on the negatively charged bacterial cell wall, and the alkyl long-chain structure can penetrate the bacterial cell membrane to destroy the physiological activities of the bacteria. Therefore, the new composite material also has permanent antibacterial properties. In addition, since the antibacterial method of the new composite material is physical antibacterial, it will not cause harm to the human body.
[0030] 3) The signal hydrogen molecule of the present invention is compatible with the composite new material and has a good adsorption effect on hydrogen, and has antibacterial properties and is not easy to breed bacteria. It also has good biocompatibility and can realize the in vivo hydrogen supply to specific lesions. Therefore, it can be widely used in the field of hydrogen medicine. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A method for preparing modified activated carbon comprises the following steps:
[0034] The activated carbon fiber with a diameter of 10 μm was washed with ultrapure water, and then heat-treated at 800°C for 4 hours under nitrogen protection. After the heat treatment, it was naturally cooled to room temperature. After cooling to room temperature, the activated carbon fiber was boiled in ultrapure water for 45 minutes to obtain modified activated carbon fiber.
[0035] Example 2
[0036] A method for preparing modified activated carbon comprises the following steps:
[0037] The activated carbon fiber with a diameter of 12 μm was washed with ultrapure water, and then heat-treated at 950°C for 5 hours under nitrogen protection. After the heat treatment, it was naturally cooled to room temperature. After cooling to room temperature, the activated carbon fiber was boiled in ultrapure water for 52 minutes to obtain modified activated carbon fiber.
[0038] Example 3
[0039] A method for preparing modified activated carbon comprises the following steps:
[0040] The activated carbon fiber with a diameter of 15 μm was washed with ultrapure water, and then heat-treated at 1100°C for 6 hours under nitrogen protection. After the heat treatment, it was naturally cooled to room temperature. After cooling to room temperature, the activated carbon fiber was boiled in ultrapure water for 60 minutes to obtain modified activated carbon fiber.
[0041] Example 4
[0042] A method for preparing a new composite material for carrying signal hydrogen molecules, comprising the following steps:
[0043] Step 1: 3 g of the modified activated carbon fiber obtained in Example 1, 20 g of dimethyl sulfoxide, and 2.1 g of epichlorohydrin were added to a container, and after stirring evenly, 10 g of a sodium hydroxide aqueous solution with a molar concentration of 4 mol / L was added to the container, and the mixture was reacted at a temperature of 50° C. for 3 h, and then vacuum filtered. The solid obtained by filtration was washed with ethanol and dried to obtain an intermediate 1;
[0044] Step 2: 3 g of intermediate 1, 1.4 g of 3-aminopropyltriethoxysilane and 30 g of dioxane were added into a container, stirred evenly, and reacted at 50°C for 6 h. After the reaction was completed, vacuum filtration was performed, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 2;
[0045] Step 3: Add 3g of intermediate 2, 1.6g of chlorododecane, and 15g of 2mol / L sodium hydroxide ethanol solution into a container, stir evenly, and react at 80°C for 72h. After the reaction is completed, vacuum filter, wash the solid obtained by filtration with ethanol, and dry to obtain the new composite material.
[0046] Example 5
[0047] A method for preparing a new composite material for carrying signal hydrogen molecules, comprising the following steps:
[0048] Step 1: 3 g of the modified activated carbon fiber obtained in Example 2, 22 g of dimethyl sulfoxide, and 2.2 g of epichlorohydrin were added to a container, and after stirring evenly, 12 g of a sodium hydroxide aqueous solution with a molar concentration of 4 mol / L was added to the container, and the mixture was reacted at a temperature of 50° C. for 3 h, and then vacuum filtered. The solid obtained by filtration was washed with ethanol and dried to obtain an intermediate 1;
[0049] Step 2: 3 g of intermediate 1, 1.5 g of 3-aminopropyltriethoxysilane and 33 g of dioxane were added into a container, stirred evenly, and reacted at 50°C for 6 h. After the reaction was completed, vacuum filtration was performed, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 2;
[0050] Step 3: Add 3g of intermediate 2, 1.7g of chlorododecane and 17g of 2mol / L sodium hydroxide ethanol solution into a container, stir evenly, react at 80°C for 72h, vacuum filter after the reaction, wash the solid obtained by filtration with ethanol and dry to obtain the new composite material.
[0051] Example 6
[0052] A method for preparing a new composite material for carrying signal hydrogen molecules, comprising the following steps:
[0053] Step 1: 3 g of the modified activated carbon fiber obtained in Example 3, 25 g of dimethyl sulfoxide, and 2.4 g of epichlorohydrin were added to a container, and after stirring evenly, 15 g of a sodium hydroxide aqueous solution with a molar concentration of 4 mol / L was added to the container, and the mixture was reacted at a temperature of 50° C. for 3 h, and then vacuum filtered. The solid obtained by filtration was washed with ethanol and dried to obtain an intermediate 1;
[0054] Step 2: 3 g of intermediate 1, 1.6 g of 3-aminopropyltriethoxysilane and 35 g of dioxane were added into a container, stirred evenly, and reacted at 50°C for 6 h. After the reaction was completed, vacuum filtration was performed, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 2;
[0055] Step 3: Add 3g of intermediate 2, 1.8g of chlorododecane, and 20g of ethanol solution of sodium hydroxide with a molar concentration of 2 mol / L into a container, stir evenly, and react at a temperature of 80°C for 72h. After the reaction is completed, vacuum filter, wash the solid obtained by filtration with ethanol, and dry to obtain the composite new material.
[0056] Example 7
[0057] A method for preparing a new composite material for carrying signal hydrogen molecules, comprising the following steps:
[0058] Step 1: 3 g of lignin, 23 g of dimethyl sulfoxide, and 2.1 g of epichlorohydrin were added to a container, stirred evenly, and then 13 g of a 4 mol / L sodium hydroxide aqueous solution was added to the container. After reacting at 50° C. for 3 h, the mixture was vacuum filtered, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 1.
[0059] Step 2: 3 g of intermediate 1, 1.5 g of 3-aminopropyltriethoxysilane and 31 g of dioxane were added into a container, stirred evenly, and reacted at 50°C for 6 h. After the reaction was completed, vacuum filtration was performed, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 2;
[0060] Step 3: Add 3g of intermediate 2, 1.7g of chlorododecane, and 18g of 2mol / L sodium hydroxide ethanol solution into a container, stir evenly, react at 80°C for 72h, and vacuum filter after the reaction. Wash the solid obtained by filtration with ethanol and dry it to obtain the new composite material.
[0061] Example 8
[0062] A method for preparing a new composite material for carrying signal hydrogen molecules, comprising the following steps:
[0063] Step 1: 3 g of histone, 23 g of dimethyl sulfoxide, and 2.4 g of epichlorohydrin were added to a container, stirred evenly, and then 15 g of a 4 mol / L sodium hydroxide aqueous solution was added to the container. After reacting at 50° C. for 3 h, the mixture was vacuum filtered, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 1;
[0064] Step 2: 3 g of intermediate 1, 1.4 g of 3-aminopropyltriethoxysilane and 30 g of dioxane were added into a container, stirred evenly, and reacted at 50°C for 6 h. After the reaction was completed, vacuum filtration was performed, and the solid obtained by filtration was washed with ethanol and dried to obtain intermediate 2;
[0065] Step 3: Add 3g of intermediate 2, 1.8g of chlorododecane, and 15g of 2mol / L sodium hydroxide ethanol solution into a container, stir evenly, and react at 80°C for 72h. After the reaction is completed, vacuum filter, wash the solid obtained by filtration with ethanol, and dry to obtain the new composite material.
[0066] Experimental Example 1
[0067] The signal hydrogen molecule obtained in Example 4 was injected with hydrogen and then added into a test tube together with warm water at 36°C in a mass ratio of 3%. The generated hydrogen flow was tested with a flow meter, and it was calculated that the hydrogen supply capacity of the signal hydrogen molecule-carrying composite new material was 6.2 mmol / g, and the effective hydrogen supply time was 17 days.
[0068] Experimental Example 2
[0069] The signal hydrogen molecule obtained in Example 5 was injected with hydrogen and then added into a test tube together with warm water at 36°C in a mass ratio of 3%. The generated hydrogen flow rate was tested with a flow meter, and it was calculated that the hydrogen supply capacity of the signal hydrogen molecule-carrying composite new material was 5.8 mmol / g, and the effective hydrogen supply time was 15 days.
[0070] Experimental Example 3
[0071] The signal hydrogen molecule obtained in Example 6 was injected with hydrogen and then added into a test tube together with warm water at 36°C in a mass ratio of 3%. The flow rate of hydrogen generated was tested with a flow meter, and it was calculated that the hydrogen supply capacity of the signal hydrogen molecule-carrying composite new material was 7.6 mmol / g, and the effective hydrogen supply time was 23 days.
[0072] Experimental Example 4
[0073] The signal hydrogen molecule obtained in Example 7 was injected with hydrogen and then added into a test tube together with warm water at 36°C in a mass ratio of 3%. The generated hydrogen flow rate was tested with a flow meter, and it was calculated that the hydrogen supply capacity of the signal hydrogen molecule-carrying composite new material was 3.1 mmol / g, and the effective hydrogen supply time was 7 days.
[0074] Experimental Example 5
[0075] The signal hydrogen molecules obtained in Example 8 were injected with hydrogen and then added into a test tube together with warm water at 36°C in a mass ratio of 3%. The generated hydrogen flow was tested with a flow meter, and it was calculated that the hydrogen supply capacity of the signal hydrogen molecules carrying the composite new material was 2.8 mmol / g, and the effective hydrogen supply time was 9 days.
[0076] It can be seen from Experimental Examples 1-5 that the hydrogen supply capacity of the signal hydrogen molecule-compatible composite new material prepared by the present invention is in the range of 2.8-7.6 mmol / g, which is much higher than the hydrogen supply capacity of hydrogen-rich water (0.8 μmol / g), and the effective hydrogen supply time is in the range of 7-23 days, which is much higher than the effective hydrogen supply time of hydrogen-rich water (about 3h), which proves that this method has an obvious effect on the preparation of signal hydrogen molecule-compatible composite new materials.
[0077] Experimental Example 6
[0078] The signal hydrogen molecule-matched composite new material obtained in Example 4 was tested for antibacterial properties according to standard QB / T 2850-2007. The test showed that the antibacterial rate of the composite new material against Escherichia coli was 99.17% and the antibacterial rate against Staphylococcus aureus was 94.69% at room temperature.
[0079] Experimental Example 7
[0080] The signal hydrogen molecule-matched composite new material obtained in Example 5 was tested for antibacterial properties according to standard QB / T 2850-2007. The test showed that the antibacterial rate of the composite new material against Escherichia coli was 99.59% and the antibacterial rate against Staphylococcus aureus was 96.23% at room temperature.
[0081] Experimental Example 8
[0082] The signal hydrogen molecule-matched composite new material obtained in Example 6 was tested for antibacterial properties according to standard QB / T 2850-2007. The test showed that the antibacterial rate of the composite new material against Escherichia coli was 99.09% at room temperature, and the antibacterial rate against Staphylococcus aureus was 95.97%.
[0083] Experimental Example 9
[0084] The signal hydrogen molecule-matched composite new material obtained in Example 6 was tested for antibacterial properties according to standard QB / T 2850-2007. The test showed that the antibacterial rate of the composite new material against Escherichia coli was 98.12% at room temperature, and the antibacterial rate against Staphylococcus aureus was 93.11%.
[0085] Experimental Example 10
[0086] The signal hydrogen molecule-matched composite new material obtained in Example 6 was tested for antibacterial properties according to standard QB / T 2850-2007. The test showed that the antibacterial rate of the composite new material against Escherichia coli was 97.68% and the antibacterial rate against Staphylococcus aureus was 91.39% at room temperature.
[0087] It can be seen from Experimental Examples 5-10 that the signal hydrogen molecule-compatible composite new material prepared by the present invention has good antibacterial effects on Escherichia coli and Staphylococcus aureus, with the antibacterial rate on Escherichia coli being above 98%, and the antibacterial rate on Staphylococcus aureus being above 91%, proving that the signal hydrogen molecule-compatible composite new material prepared by this method has good antibacterial effects.
[0088] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a new composite material for signal hydrogen molecules, comprising the following steps: The first step: washing the activated carbon fiber with ultrapure water, and then heat-treating it under nitrogen protection. After the heat treatment, the activated carbon fiber is naturally cooled to room temperature. After cooling to room temperature, the activated carbon fiber is placed in ultrapure water and boiled to obtain modified activated carbon fiber; Step 2: Add the modified activated carbon fiber, dimethyl sulfoxide and epichlorohydrin into a container, mix them evenly, then add sodium hydroxide solution into the container, and then react at 50°C for 3h to obtain intermediate 1; Step 3: Add intermediate 1, 3-aminopropyltriethoxysilane and dioxane into a container and react at 50°C for 6 hours to obtain intermediate 2; Step 4: Add intermediate 2, chlorododecane and sodium hydroxide solution into a container, and react at 80° C. for 72 hours to obtain the new composite material.
2. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The activated carbon fibers used in the first step have a diameter of 10-15 μm.
3. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The temperature condition of the heat treatment in the first step is 800-1100°C.
4. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The time condition of heat treatment in the first step is 4-6h.
5. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The boiling time in ultrapure water after the heat treatment in the first step is 45-60 minutes.
6. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The sodium hydroxide solution in the second step is a sodium hydroxide aqueous solution with a molar concentration of 4 mol / L.
7. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The amount ratio of the modified activated carbon fiber, dimethyl sulfoxide, epichlorohydrin and sodium hydroxide solution used in the second step is: 3g:20-25g:2.1-2.4g:10-15g.
8. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The usage ratio of the intermediate 1, 3-aminopropyltriethoxysilane and dioxane used in the third step is: 3g:1.4-1.6g:30-35g.
9. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The sodium hydroxide solution in the fourth step is a sodium hydroxide ethanol solution with a molar concentration of 2 mol / L, and the amount ratio of the intermediate 2, chlorododecane, and sodium hydroxide solution used is 3g:1.6-1.8g:15-20g.
10. The method for preparing a new composite material for carrying signal hydrogen molecules according to claim 1, characterized in that: The first and second steps in the preparation method can be replaced by: adding a fiber structure with a hydroxyl group or a protein structure with a hydroxyl group, dimethyl sulfoxide, and epichlorohydrin into a container, mixing them evenly, adding a sodium hydroxide solution into the container, and then reacting at a temperature of 50° C. for 3 hours to obtain intermediate 1.
Citation Information
Patent Citations
Preparation method of nickel oxide loaded modified activated carbon fiber adsorbent
CN110975814A
Hydroxyl modified carbon catalytic hydrogenation material based on hydrogen overflow as well as preparation method and application of hydroxyl modified carbon catalytic hydrogenation material
CN115138355A